2014
DOI: 10.1159/000362937
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Diffusion Tensor Imaging-Based Tractography into Deep Brain Stimulation Surgery: A Review of the Literature

Abstract: Background: It has been generally accepted that deep brain stimulation (DBS) not only acts in the nucleus where it is being applied, as initially thought, but that chronic stimulation activates axons located in its scope, and that this activation can exert its effects in distant areas. Considering this, DBS target identification should be made based on techniques that identify white matter tracts, such as tractography, rather than only by identifying specific nuclei on conventional magnetic resonance imaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Although it is generally agreed on that effects of DBS are exerted on fibers, there is only limited published evidence on DTI tractography-assisted stereotactic surgery [23]. A post hoc study of our group in 11 patients who received Vim-DBS was able to show that effective electrode positions are located inside or within proximity of the DRT [12], extending knowledge gathered by Klein et al [24] and Coenen et al [10,11].…”
Section: Discussionsupporting
confidence: 72%
“…Although it is generally agreed on that effects of DBS are exerted on fibers, there is only limited published evidence on DTI tractography-assisted stereotactic surgery [23]. A post hoc study of our group in 11 patients who received Vim-DBS was able to show that effective electrode positions are located inside or within proximity of the DRT [12], extending knowledge gathered by Klein et al [24] and Coenen et al [10,11].…”
Section: Discussionsupporting
confidence: 72%
“…Although some studies show unaltered forniceal white matter in depression [72], future forniceal subregional analysis may help explain these discrepancies [73]. Although the mechanisms through which DBS exerts its impact are complex and incompletely understood [74], growing evidence supports a greater influence on diffuse white matter tracts, compared to gray matter, suggesting that methods focused on improving tract visualization, such as tractography, will be of great importance in DBS target planning in future [75]. Together, these results show that poorer pre-DBS dMRI metrics (i.e.…”
Section: Implications For Using Dmri and Dbs In Anorexia Nervosamentioning
confidence: 99%
“…Also, as DBS does not result in clinical improvements for all people with major depressive disorder [62,77], it will be important going forward to precisely determine which anorexia nervosa patients respond best to DBS. Regardless, it appears that dMRI techniques, including mutli-tensor tractography, will be key in determining the best targeting for such effects and may eventually become part of standard pre-surgical planning [75,78,79].…”
Section: Implications For Using Dmri and Dbs In Anorexia Nervosamentioning
confidence: 99%
“…Similarly, the effect of deep brain stimulation (DBS) is predicted by connectomics and may be mediated by white matter. 36,48,58,84 Thus, Figee et al demonstrated that stimulation of the nucleus accumbens in obsessive-compulsive disorder normalized nucleus accumbens activity but also critically reduced its increased (functional) connectivity with the prefrontal cortex as well as frontal low-frequency oscillations during symptoms. 31 Regarding depression, DBS targeting the subgenual cortex/subcallosal cingulate cortex (which is currently the most effective target) is mediated by its impact on white matter rather than by direct cortical activations.…”
Section: Toward Individually Targeted Psychosurgerymentioning
confidence: 99%